Implicit Theories and Engagement in Math Among Chinese Adolescent Students: A Moderated Mediation Model of Intrinsic Value and Academic Self-Efficacy - Jiang, Shuyang; Liu, Ru-De; Ding, Yi; Fu, Xinchen; Sun, Yan; Jiang, Ronghuan; Hong, Wei (Frontiers in Psychology, 2020)
Recent studies have established associations between students' implicit theories and their academic engagement. However, there is still limited understanding of the potential mechanisms of this relation, and whether it works for students in the context of mathematics as well as in other subjects. The current study aimed to fill this gap by conducting a two-wave survey examining a moderated mediation model concerning the psychological mechanisms that account for the association between students’ implicit theories and mathematics engagement. Applying the theoretical framework of implicit theory, we hypothesized that intrinsic value would be a possible mediating variable between students' implicit theories and academic engagement, and that students’ academic self-efficacy would moderate the link between implicit theory and intrinsic value. A sample of 710 Chinese adolescent students self-reported their implicit theory, intrinsic value, and academic self-efficacy at Time 1, and engagement in math at Time 2, 12 months apart. After controlling for age and gender, the results revealed positive associations between students’ implicit theories and their engagement in math, and intrinsic value partially mediated the relation between implicit theories and engagement in math. Moreover, students’ academic self-efficacy moderated the link between implicit theory and intrinsic value. These findings contribute to the understanding of the impact of implicit theory on students’ mathematics engagement. Limitations and implications for instructional practices are discussed.